The Use Of Modern Interactive Methods As A Factor In Improving The Quality Of Education (Open Academia: Journal of Scholarly Research, 2026)
The article examines the role of interactive teaching methods in enhancing the quality of education, as well as the implementation of critical thinking development technologies in classroom practice. Particular attention is paid to the pedagogical potential of interactive approaches in fostering students’ professional competence, independence, and active engagement in the learning process.